2002
DOI: 10.1046/j.1440-1819.2002.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Falling asleep while driving and automobile accidents among patients with obstructive sleep apnea–hypopnea syndrome

Abstract: Among 448 patients with obstructive sleep apnea-hypopnea syndrome (OSAHS), 40 patients (8.9%) had been involved in one or more automobile accidents during the preceding 5 years.The main cause of these accidents was falling asleep while driving. Excessive sleepiness during driving was associated with an Epworth sleepiness scale (ESS) score of > 11 and/or an apnea-hypopnea index (AHI) of > 15. The automobile accident rate among 182 patients with severe OSAHS (AHI > 30) was significantly higher than the rate amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 5 publications
7
48
3
1
Order By: Relevance
“…We also found that excessive daytime sleepiness was associated with the prevalence of a 3% oxygen desaturation index of ≥ 15, which was consistent with the results from the Sleep Heart Health Study (25) and Wisconsin Sleep Cohort Study (26). Several clinical studies (1)(2)(3)(4) and an epidemiological study (18) have indicated that excessive sleepiness is associated with increased risk of traffic accidents in sleep-disordered breathing patients. Therefore, the detection and control of undiagnosed sleep-disordered breathing among truck drivers may have a significant impact on the prevention of cardiovascular disease and traffic accidents.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that excessive daytime sleepiness was associated with the prevalence of a 3% oxygen desaturation index of ≥ 15, which was consistent with the results from the Sleep Heart Health Study (25) and Wisconsin Sleep Cohort Study (26). Several clinical studies (1)(2)(3)(4) and an epidemiological study (18) have indicated that excessive sleepiness is associated with increased risk of traffic accidents in sleep-disordered breathing patients. Therefore, the detection and control of undiagnosed sleep-disordered breathing among truck drivers may have a significant impact on the prevention of cardiovascular disease and traffic accidents.…”
Section: Discussionsupporting
confidence: 87%
“…Several clinical studies have indicated that excessive sleepiness is associated with increased risk of traffic accidents among patients with obstructive sleep apnea-hypopnea syndrome (1)(2)(3)(4). Previous cross-sectional studies in Western countries have shown that sleep-disordered breathing is positively associated with the prevalence of hypertension (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, there has been a consensus that the periodicity of meals can affect body weight, since the metabolic efficiency of foods differs according to the time of their ingestion. (20) According to a family budget study, 40.6% of Brazilian individuals over 20 years of age are overweight. (29) Although these data (29) show a high prevalence of overweight in the general population, the prevalence was even higher (47.8%) among the drivers evaluated in adjustment variable in the model (OR = 2.46; p = 0.079), which means that individuals with OSAS have poor quality sleep due to the symptoms characteristic of the syndrome, such as daytime sleepiness.…”
Section: Resultsmentioning
confidence: 99%
“…(17) The relevance of studies of OSAS in truck drivers is related to the inability of such individuals to maintain a satisfactory level of concentration and the necessary psychomotor coordination to drive, (1) which increases the risk of accidents. (11,(19)(20)(21) The decrease in the performance of drivers has been observed by various researchers. (19,21,22) In view of what has been presented above, the objective of the present study was to determine the prevalence of and identify factors associated with OSAS in a population of truck drivers.…”
Section: Original Articlementioning
confidence: 97%
“…The inadequacy of information about Asian populations regarding this important subject encourages us to investigate whether sleep duration and snoring are associated with falling asleep or feeling sleepiness while driving. Although factors associated with falling asleep and feeling Usually (n=71) 50.7% (36) sleepiness while driving have been studied among professional drivers (21) and patients with sleep apnea syndrome (11,22) …”
Section: Introductionmentioning
confidence: 99%